Mathematical analysis and process optimization of wire and arc additive manufactured Ti6Al4V ELI alloy with in-situ rolling - Youheng Fu; Mingbo Zhang; Xi Chen; Hao Song; Jianwu Huang; Hang Lin; Wenzheng Zhai; Guilan Wang (Journal of Materials Research and Technology, 2024)
The combination of wire and arc additive manufacturing (WAAM) and rolling offer the advantages of high efficiency, low cost, and fine grain, making it a viable option for the rapid production of aerospace thin-wall forgings using titanium alloy. However, the interplay between various factors such as temperature gradient, deformation force, and prior pass morphology directly influence the morphology and grain evolution before and after subsequent pass deformations, which lead to insufficient overall morphological accuracy and grain refinement uniformity. Building upon theoretical analysis, numerical simulation, and experimental verification, this study focuses on investigating the metal flow behavior and grain evolution mechanism during WAAM with in-situ rolling single-pass multi-layers. By establishing correlations between morphology, microstructure, temperature, stress-strain and deformation characteristics, the process optimization strategies of large width-height ratio, shallow melting depth and fixed width spread were proposed. These findings can provide theoretical support for the deformation machine design and the high-precision, uniformly fine grains additive manufacturing of thin-walled titanium alloy forgings.